2022
DOI: 10.3389/fcvm.2022.992284
|View full text |Cite
|
Sign up to set email alerts
|

Identification of intrinsic genes across general hypertension, hypertension with left ventricular remodeling, and uncontrolled hypertension

Abstract: The purpose of the present article is to identify intrinsic genes across general hypertension (HT), hypertension with left ventricular remodeling (HT-LVR), and uncontrolled hypertension (UN-HT). In total, four microarray datasets (GSE24752, GSE75360, GSE74144, and GSE71994) were downloaded from the GEO database and were used to identify differentially expressed genes (DEGs), respectively. Furthermore, gene set enrichment analysis (GSEA) was utilized to screen for significantly enriched biological pathways acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Second, HNP-1 may have a "bipolar effect," such that inflammatory factor expression may be enhanced by a high dose of HNP-1 (100 μg/day) and inhibited by a healthy dose of HNP-1 (5 μg/day or 10 μg/mL) [65]. Third, studies have reported that regulation of the inflammatory response effectively controls BP and ameliorates HLVH [65][66][67][68][69][70][71]. However, NF-κB is a key regulatory signaling pathway in inflammatory immune responses [72][73][74][75], and NF-κB inhibition may ameliorate hypertension and HLVH [76][77][78][79][80][81][82][83][84][85][86].…”
Section: Discussionmentioning
confidence: 99%
“…Second, HNP-1 may have a "bipolar effect," such that inflammatory factor expression may be enhanced by a high dose of HNP-1 (100 μg/day) and inhibited by a healthy dose of HNP-1 (5 μg/day or 10 μg/mL) [65]. Third, studies have reported that regulation of the inflammatory response effectively controls BP and ameliorates HLVH [65][66][67][68][69][70][71]. However, NF-κB is a key regulatory signaling pathway in inflammatory immune responses [72][73][74][75], and NF-κB inhibition may ameliorate hypertension and HLVH [76][77][78][79][80][81][82][83][84][85][86].…”
Section: Discussionmentioning
confidence: 99%